2002
DOI: 10.1177/0165551024234093
|View full text |Cite
|
Sign up to set email alerts
|

The many applications of patent analysis

Abstract: The use of patent analysis in many different contexts is discussed. Applications discussed range from intellectual property management, to merger and acquisition targeting and due diligence, to stock market valuation. The authors draw on 38 years of combined patent-related experience to discuss a number of techniques and metrics that have been found to work well in specific situations. 50 1 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 7 publications
0
39
0
3
Order By: Relevance
“…Jaffe and Lerner [4] and Jaffe and Trajtenberg [5] provide additional reviews and critiques of patent citation analysis. Even if these references are a "noisy" indicator [6], studies show there is a strong positive correlation between citations and technological importance [7] as indicated by awards [8], expert judgement [9], and continued payment of maintenance fees [10]. Research has also found a positive relationship between patent citation indicators and business financial performance.…”
Section: Using Citation Analysis To Identify Impacts On Inventive Actmentioning
confidence: 99%
See 2 more Smart Citations
“…Jaffe and Lerner [4] and Jaffe and Trajtenberg [5] provide additional reviews and critiques of patent citation analysis. Even if these references are a "noisy" indicator [6], studies show there is a strong positive correlation between citations and technological importance [7] as indicated by awards [8], expert judgement [9], and continued payment of maintenance fees [10]. Research has also found a positive relationship between patent citation indicators and business financial performance.…”
Section: Using Citation Analysis To Identify Impacts On Inventive Actmentioning
confidence: 99%
“…In total, there are over 34,000 references to NIST research outputs between 1970 and June 2015. The plurality of these references are to NIST peer-reviewed 7 Searching the Government interest section for "NBS or Nat*bur*" identifies four patents (Patent Numbers: 4447743; 4836869; 4974113; 4987526) issued between 1975 and 1990 that were omitted from this analysis. 8 A commercially available product is identified in this paper in order to specify the experimental procedure adequately.…”
Section: Impact and Potential Use Of Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Karkioffers a survey of the various methods of patent citation analysis and their applications, outlining a number of technological indicators [16]. Anthony Brietzman and Mary Ellen Mogee consider the use of patent analysis in a number of scenarios, from corporate finance to securities valuation, offering several metrics that are useful in a number of situations [17]. Michael Roach and Wesley Cohen look at the validity of patent citation information as a measure of knowledge-flow, and in particular the validity of backwards citation information [18].…”
Section: Intellectual Property and Economic Estimation: A Precismentioning
confidence: 99%
“…This does not mean that all important patents are highly cited, nor that every highly cited patent is important. However, numerous validation studies have revealed the existence of a strong positive relationship between citations and technological importance (see Breitzman and Mogee (2002) for a review of validation studies). For example , Carpenter et.…”
Section: Introductionmentioning
confidence: 99%